Accountability, Transparency, Managerial Attitude and Muzakki’s Trust: A Study on the Zakat Amil Institution of Jogokariyan Mosque, Yogyakarta - Nada Shafiyyah; Annisa Fithria (At-Taqaddum, 2023)
Trust is an essential aspect to be fostered between muzakki (those who contribute zakat) and zakat amil institutions to optimize zakat collection. Accountability, financial report transparency, and managerial attitude are crucial for zakat amil institutions to enhance muzakki's trust. This research aims to examine the influence of accountability, financial report transparency, and managerial attitude on the level of muzakki's trust in the Zakat Amil Institution of Jogokariyan Mosque, Yogyakarta. This study utilized nonprobability sampling with an incidental sampling approach. The data used were primary data collected through questionnaires distributed to 60 respondents who are muzakki contributing zakat to the Zakat Amil Institution of Jogokariyan Mosque, Yogyakarta. The results of the research indicate that accountability, financial report transparency, and managerial attitude have a positive influence on the level of muzakki's trust in the Zakat Amil Institution of Jogokariyan Mosque, Yogyakarta